2023
DOI: 10.1002/cbdv.202301269
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Potential Antimicrobial and Anti‐Inflammatory Activities of Essential Oil from Fruits of Alpinia zerumbet (Pers.) B.L.Burtt & R.M.Sm.

Jiaojiao Hou,
Huxuan Gong,
Zan Gong
et al.

Abstract: Alpinia zerumbet (Pers.) B.L.Burtt & R.M.Sm. was extensively used in traditional medicine for its several properties, but continuous investigation is needed to discover the properties of its essential oils (EOs). This work evaluated the properties of an EO obtained by steam distillation (named ESD) as well as extracts obtained by petroleum ether (named EP) both from Alpinia zerumbet fruits. Gas chromatography‐mass spectrometry (GC‐MS) was chosen to identify the composition, and eleven compounds were identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The essential oils of A. zerumbet mainly include monoterpenes, oxygenated monoterpenes, and oxygenated sesquiterpenes [ 123 ]. According to the previous 35 studies [ 2 , 4 , 8 , 14 , 18 , 31 , 34 , 36 , 37 , 38 , 41 , 47 , 49 , 51 , 52 , 53 , 54 , 70 , 74 , 87 , 92 , 96 , 97 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 ], the relative contents of the 33 major volatile components in the essential oils prepared from the leaves [ 2 , 4 , 8 , 14 , 31 , 34 , 36 , 37 , 38 , 41 , 47 , 49 , 51 , 52 , …”
Section: Phytochemicalsmentioning
confidence: 99%
See 4 more Smart Citations
“…The essential oils of A. zerumbet mainly include monoterpenes, oxygenated monoterpenes, and oxygenated sesquiterpenes [ 123 ]. According to the previous 35 studies [ 2 , 4 , 8 , 14 , 18 , 31 , 34 , 36 , 37 , 38 , 41 , 47 , 49 , 51 , 52 , 53 , 54 , 70 , 74 , 87 , 92 , 96 , 97 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 ], the relative contents of the 33 major volatile components in the essential oils prepared from the leaves [ 2 , 4 , 8 , 14 , 31 , 34 , 36 , 37 , 38 , 41 , 47 , 49 , 51 , 52 , …”
Section: Phytochemicalsmentioning
confidence: 99%
“…The chemical constituents in the essential oils of A. zerumbet fruits have been reported by the groups of Shen et al [ 88 , 92 ], Feng et al [ 53 ], and Hou et al [ 87 ]. The group of Shen et al [ 88 , 92 ] identified 58 volatile compounds in the essential oils of A. zerumbet fruits collected from China.…”
Section: Phytochemicalsmentioning
confidence: 99%
See 3 more Smart Citations